2012
DOI: 10.1111/j.1530-0277.2012.01910.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Dynamic Gene Expression Changes in the Central Nucleus of the Amygdala During Alcohol Withdrawal

Abstract: Background Chronic alcohol use causes widespread changes in the cellular biology of the amygdala's central nucleus (CeA), a GABAergic center that integrates autonomic physiology with the emotional aspects of motivation and learning. While alcohol-induced neurochemical changes play a role in dependence and drinking behavior, little is known about the CeA's dynamic changes during withdrawal, a period of emotional and physiologic disturbance. Methods We used a qRT-PCR platform to measure 139 transcripts in 92 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 58 publications
(84 reference statements)
4
23
1
Order By: Relevance
“…In the LgA-7day group, this would suggest that increasing withdrawal severity was necessary to induce the proposed dysregulation in the KOR-JNK pathway. Interestingly, withdrawal from chronic alcohol use decreased JNK mRNA expression in the CeA (45).…”
Section: Discussionmentioning
confidence: 95%
“…In the LgA-7day group, this would suggest that increasing withdrawal severity was necessary to induce the proposed dysregulation in the KOR-JNK pathway. Interestingly, withdrawal from chronic alcohol use decreased JNK mRNA expression in the CeA (45).…”
Section: Discussionmentioning
confidence: 95%
“…Chronic alcohol exposure produces neuroadaptations in glutamatergic transmission in the CeA 170, 171 , and GluN2B-containing GluNs are most sensitive to CIE 170, 172, 173 . CIE, but not continuous vapor exposure, increases BNST GluN-mediated EPSCs, not from altered glutamate release but from an increase in GluN2-containing GluN 174 , suggesting that repeated cycles of exposure and withdrawal are necessary for these adaptations to occur.…”
Section: Heavy Drinking and Withdrawalmentioning
confidence: 99%
“…Both addiction and withdrawal have pathologies and comorbidities that are associated with distinct changes in brain function and physiology. In previous work we found the status of alcohol withdrawal produces a robust and sustained neuroinflammatory response in the central nucleus of the amygdala (CeA), a structure strongly associated with regulation of emotion (Freeman et al 2012, 2013). We and others have suggested that the effects of inflammation on neuronal function drive some of the autonomic disturbances, anxiety, and other negative feelings associated with withdrawal (Retson et al 2014).…”
Section: Introductionmentioning
confidence: 99%